INTERMEDIAL TEXTURES: GILBERTO FREYRE: SOCIOLOGIST, POET, PAINTER - Ribeiro Oliveira, Solange (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2020)
Relying on the concepts of intermediality, ekphrasis and intermedial reference, the essay discusses Gilberto Freyre’s vast œuvre as that of a multiple artist, working in different areas ”“ poetry, painting, literary prose ”“ as well as the author of groundbreaking contributions to the social sciences. The article especially underscores the close relationships between his output in the verbal and in the visual arts, remarkable for their constant reference to events, characters and landscapes analyzed in his sociological texts. In this context, the whole of Freyre’s production may be taken as a multiple, kaleidoscopic text, which, in different media, explores close- knit themes.